2012
DOI: 10.1007/s00192-012-1969-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for reoperation of surgically treated urinary incontinence

Abstract: Introduction and hypothesis The objective of our study was to estimate the incidence and to identify the risk factors for reoperation of surgically treated stress urinary incontinence (SUI). Methods We conducted a nested case-control study among 1,132 women who underwent SUI surgery from January 1988 to June 2007. Cases (n035) were women who required reoperation for SUI following the first intervention up to December 2008. Controls (n089) were women randomly selected from the same cohort who did not require re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…According to our results and due to the fact that some authors showed worse results of anti‐incontinence procedures in obese patients indicating the group at risk for failure those groups require special attention . At the same time, more than one vaginal delivery was shown to be an important risk factor for reoperation (adjusted odds ratio [OR] 3.5; 95% confidence interval [CI] 1.0‐12.6) . It is likely that worse effectiveness of mid‐urethral sling procedures in the above group of patients might be connected with atypical UL.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…According to our results and due to the fact that some authors showed worse results of anti‐incontinence procedures in obese patients indicating the group at risk for failure those groups require special attention . At the same time, more than one vaginal delivery was shown to be an important risk factor for reoperation (adjusted odds ratio [OR] 3.5; 95% confidence interval [CI] 1.0‐12.6) . It is likely that worse effectiveness of mid‐urethral sling procedures in the above group of patients might be connected with atypical UL.…”
Section: Discussionmentioning
confidence: 53%
“…22 At the same time, more than one vaginal delivery was shown to be an important risk factor for reoperation (adjusted odds ratio [OR] 3.5; 95% confidence interval [CI] 1.0-12.6). 23 It is likely that worse effectiveness of mid-urethral sling procedures in the above group of patients might be connected with atypical UL.…”
Section: Discussionmentioning
confidence: 98%
“…The median time for repeat anti‐incontinence surgery was 2.8 years . On the other hand, a case‐control study among from Switzerland reported a cumulative SUI reoperation incidence of 3.1% with a mean 10.9 years follow‐up . In the current population‐based cohort with a mean follow‐up of 86 months, the overall reoperation rate of 3.850% was relatively low, which may partially be explained by the shorter follow‐up duration.…”
Section: Discussionmentioning
confidence: 58%
“…13 On the other hand, a case-control study among from Switzerland reported a cumulative SUI reoperation incidence of 3.1% with a mean 10.9 years follow-up. 14 In the current population-based cohort with a mean follow-up of 86 months, the overall reoperation rate of 3.850% was relatively low, which may partially be explained by the shorter follow-up duration. However, the incidence rate of 54.37 per 10,000 PY was close to the previously reported figures.…”
Section: Discussionmentioning
confidence: 99%